Efektivitas Penyediaan Informasi Dan Penyaluran Tenaga Kerja (Studi Kasus BKK SMKN 1 Batam) - Aldy Wiguna; Rumzi Samin; Fitri Kurnianingsih (Doktrin:Jurnal Dunia Ilmu Hukum dan Politik, 2023)
Special Job Exchanges, hereinafter abbreviated as BKK, are service units in secondary education units, higher education units, and job training institutions that provide manpower placement facilities to graduates related to the availability of job vacancies, data collection related to prospective workers, carry out debriefing and guidance activities, which Lastly is assistance. The Batam 1 SMK Negeri 1 Special Job Exchange has established partnerships or collaborations with 125 industrial companies, not only for apprenticeships, but also for job vacancies for graduates of SMKN 1 Batam. The purpose of this study is to determine the effectiveness of providing information and distributing labor (Case study of BKK SMKN 1 Batam). This study uses a qualitative descriptive research method. The data source for this research comes from primary data (18 informants) and secondary data (sourced from BKK). The results of the study were based on (1) indicators of achieving goals in an effort to increase the number of graduates being absorbed from special job fairs were not yet effective, (2) indicators of integration were already effective in terms of program socialization, and (3) indicators of adaptation from observations during the field showed that they had been effective. The conclusion of this study concludes that BKK is quite effective but its implementation has not been optimal. The suggestion from this research is to renew the strategy of the job market specifically in attracting companies to be able to recruit graduates so that the percentage of working graduates can increase every year.